¿Quién habla cuando escribe Maquiavelo? = Who speaks when Maquiavelo writes? - Durán, Alcira Rosa (2018)
El presente artículo, consiste en un Avance de Investigación del campo de la ciencia política, relativo a la vida y obra de Nicolás Maquiavelo, cuya finalidad es intentar desentrañar la conflictiva relación del autor con el contexto político del siglo XVI y la aplicabilidad de sus aportes políticos, en el presente. The present article is based on research, currently in progress, in the field of political science. It focuses on Nicolas Maquiavelo’s life and work, and it seeks to unravel the author’s difficult relation, with the 15th century political context, and the relevance of his political contributions, at the present time. --